Substrate Specificity of ABCB Transporters Predicted by Docking Simulations Can Be Confirmed by Experimental Tests - Mario Röpcke; Sha Lu; Cäcilia Plate; Fee Meinzer; Antonia Lisiecki; Susanne Dobler (Molecules)
ATP-binding cassette (ABC) transporters, particularly those of subfamily B, are involved in cell detoxification, multidrug resistance, drug treatment pharmacodynamics, and also ecological adaptation. In this regard, ABCB transporters may play a decisive role in the co-evolution between plants and herbivores. Cardenolides, toxic steroid glycosides, are secondary plant metabolites that defend plants against herbivores by targeting their sodium–potassium ATPase. Despite their toxicity, several herbivorous insects such as the large milkweed bug (Oncopeltus fasciatus) have evolved adaptations to tolerate cardenolides and sequester them for their own defense. We investigate the role of two ABCB transporters of O. fasciatus for the paracellular transport of cardenolides by docking simulations and ATPase assays. Cardenolide binding of OfABCB1 and OfABCB2 is predicted by docking simulations and calculated binding energies are compared with substrate specificities determined in ATPase assays. Both tested ABCB transporters showed activity upon exposure to cardenolides and Km values that agreed well with the predictions of our docking simulations. We conclude that docking simulations can help identify transporter binding regions and predict substrate specificity, as well as provide deeper insights into the structural basis of ABC transporter function.